2014
DOI: 10.1002/celc.201402291
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Independent Glycerol Electrooxidation Behavior on Different Ordered Domains of Polycrystalline Platinum

Abstract: We investigate the electrooxidation of glycerol (GlOH) on polycrystalline Pt. The results obtained in the presence of GlOH were compared with those of fresh and disturbed low‐index Pt single crystals [(111), (100) and (110)]. Monitoring of the oxidation currents of GlOH by cyclic voltammetry on the different surfaces revealed that the electrooxidation of GlOH is highly sensitive to the order of the polycrystalline Pt atoms. Interestingly, after being disturbed by the application of voltammetric cycles, the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 25 publications
4
51
1
4
Order By: Relevance
“…Analogously, the ethanol electrooxidation reaction on Pt electrodes also show high degree of electrode deactivation under high pH . In addition, when compared with results obtained in acidic solutions, the voltammetric profile of GEOR in alkaline medium is significantly different, showing higher electroactivity, independently of the surface orientation used …”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Analogously, the ethanol electrooxidation reaction on Pt electrodes also show high degree of electrode deactivation under high pH . In addition, when compared with results obtained in acidic solutions, the voltammetric profile of GEOR in alkaline medium is significantly different, showing higher electroactivity, independently of the surface orientation used …”
Section: Resultsmentioning
confidence: 76%
“…In an recent communication is showed that after the first cycle the Pt(111) electrode has a dramatic deactivation, lowering its electroactivity to about 10 % of the highest faradaic response . In acidic media, the GEOR on Pt electrodes follow a similar trend as observed in basic media, in a much less extent …”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations